ANALISIS PEMBELAJARAN SUB POKOK FUNGSI MATEMATIKA EKONOMI TERHADAP FUNGSI PERMINTAAN DAN PENAWARAN PADA MAHASISWA UNIVERSITAS PEMBANGUNAN PANCA BUDI - , Mika Debora Br. Barus (Jurnal Akuntansi Bisnis dan Publik, 2020)
This article discusses the results of research into the application of sub-functions in economic mathematics to the demand function and supply function. Material functions are often used by experts in solving economic problems. The purpose of this study was to determine student activity during sub-function learning in economic mathematics to the demand function and supply function, to determine the response of students when learning the function in economic mathematics to the demand function and supply function. The research method used was a quasi-experimental, the research design was a one-shot case study. The population of this research is all accounting students of the Faculty of Social Sciences University of Panca Budi Development University and the sample is the first semester students of accounting at the Panca Budi Development University. The statistics used in this study are descriptive statistics with the analyzed data are qualitative data. The research instrument used was observation of student activities and observations of lecturer activities in teaching, interviews, and Likert scale questionnaires. Based on the analysis of the student observation sheet, student activities during the learning sub-function of economic mathematics to the demand and supply function sub-functions increase. Based on the analysis of the questionnaire, students responded positively to learning sub-functions in economic mathematics to the demand function and supply function.